Symptomatic Renal Artery Stenosis and Infra-renal AAA. Issue 5 (May 2015) - Benson, R.A.; Paraskevas, K.I.; Patterson, B.O.; Loftus, I.M.
<x xml:space="preserve">Abstract</x> Objectives To identify evidence to guide the vascular surgeon as to the relevance of renal artery stenting in a patient with symptomatic renal artery stenosis undergoing elective endovascular aortic aneurysm repair (EVAR). Methods A comprehensive literature search of MEDLINE was performed without time limits. The following terms were used in the first instance: renal artery stenting and renal artery stenosis, and any other analogous terms identified during the search. Selection criteria were set to randomised control trials. Results Despite several large, randomised controlled trials investigating renal artery stenting against medical treatment alone in symptomatic renal artery stenosis, there has been no significant benefit identified in terms of improvement in renal function, control of blood pressure, or need for dialysis. The stented populations were also more likely to suffer from complications caused by the procedure such as bleeding, cholesterol embolisation and flash pulmonary oedema. Conclusion There is no evidence for the use of renal artery stenting over optimal medical management in the treatment of patients with symptomatic atherosclerotic renal artery stenosis, irrelevant of the degree of stenosis. In the setting of EVAR, prevention of deterioration of renal function should be with involvement of the renal physicians, adequate hydration, and use of minimal contrast agent. Repair should be undertaken in centres with access to 24-hour haemofiltration services.